QT dispersion and electrocardiographic changes in women with gestational diabetes mellitus - Medová, Eva; Fialová, E; Mlček, Mikuláš; Slavíček, Jaroslav; Dohnalová, Alena; Charvát, Jiří; Žákovičová, Eva; Kittnar, Otomar (Physiological research, 2012)
Gestational diabetes mellitus (GDM) represents additional risks to both mother and infant. Moreover it increases a woman's risk of cardiovascular disease in the postpartum. The aim of our study was therefore to detect changes of both the QT dispersion and the electrical heart field that could be typical for GDM. Body surface potential maps were obtained using the Cardiac 112.2 device from 26 young women with GDM and 54 young healthy pregnant women in the 36th week of pregnancy. The same recordings were obtained from 18 healthy women in the same age (19-36 years). The average QT dispersion (±SD) in women suffering from GDM was significantly higher (107±25 ms) both than in those with physiological pregnancy (73±18 ms) and than in the normal subjects (34±12 ms) (P<0.001). Moreover we have found in GDM patients shorter QRS complex 82.0±6.8 ms vs. 89.5±8.2 ms in healthy pregnant women and 90.8±7.9 ms in the control group (p=0.011), more horizontal electrical heart axis [16.4±20.1° vs. 42.4±28.7° and 74.6±39.2° respectively (P<0.05)] and lower some depolarization and repolarization amplitudes on isopotential and isointegral maps. According to these results we suppose that described electrocardiographic changes reflect a deterioration of the complete process of ventricular depolarization and repolarization in GDM.
Keywords: Pregnancy Trimester, Third; elektrokardiografie; dospělí; Adult; lidé; Heart Ventricles; těhotenství; gestační diabetes; srdeční komory; Pregnancy; Pregnancy Complications; třetí trimestr těhotenství; Humans; komplikace těhotenství; Electrocardiography; Diabetes, Gestational; ženské pohlaví; Female